Synthetic charts to control bivariate processes with autocorrelated data. (July 2016) - Simões, Felipe Domingues; Leoni, Roberto Campos; Machado, Marcela Aparecida Guerreiro; Costa, Antonio Fernando Branco
Highlights: We consider the monitoring of bivariate processes with autocorrelated data. The use of two side-sensitive X ‾ charts compete well with the synthetic T 2 chart. The Markov chain approach was used to obtain the steady-state properties. The synthetic rules always improve the performance of the control charts. Abstract: In this study, we propose the use of simultaneous X ‾ charts to control bivariate processes with autocorrelated data. The first set of X ‾ charts is side-sensitive with regard to the same variable (SV X ‾ charts) and the second one is side-sensitive with regard to both variables (BV X ‾ charts). The Markov chain approach was used to obtain the steady-state properties of the X ‾ charts. In comparison with the standard synthetic T 2 chart, the SV and the BV charts signal faster in a wide variety of disturbances, except when the variables are high correlated. The BV charts are simpler and signal faster than the SV charts.